2000
DOI: 10.1007/bf02439276
|View full text |Cite
|
Sign up to set email alerts
|

Combined disorders in erythro- and immunopoiesis in (C57Bl/6xDBA/2)F1 mice with immunodeficiency induced by graft-versus-host reaction and immunocomplex glomerulonephritis

Abstract: Disorders in erythro- and immunopoiesis were studied in B6D2F1 mice with immunodeficiency induced by graft versus host reaction and with immunocomplex glomerulonephritis. By the 6th-7th months of the disease the animals developed anemia accompanied by enhanced phagocytic activity of macrophages and production of tumor necrosis factor. Macrophage dysfunction is presumed to be a cause of anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A decrease in the number of erythrocytes and hemoglobin, a decrease in hematocrit and a parallel increase in the number of reticulocytes in the blood of mice with cGVHD is in good agreement with our earlier conclusion that these animals have autoimmune hemolytic anemia [5,11]. In our previous studies, this conclusion was also confirmed by high Coombs test values, indicating the production of a large number of anti-erythrocyte antibodies during the development of cGVHD, and an increase in the amounts of erythroid precursors in the bone marrow, which directly indicates the stimulation of erythropoiesis in these animals [5].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A decrease in the number of erythrocytes and hemoglobin, a decrease in hematocrit and a parallel increase in the number of reticulocytes in the blood of mice with cGVHD is in good agreement with our earlier conclusion that these animals have autoimmune hemolytic anemia [5,11]. In our previous studies, this conclusion was also confirmed by high Coombs test values, indicating the production of a large number of anti-erythrocyte antibodies during the development of cGVHD, and an increase in the amounts of erythroid precursors in the bone marrow, which directly indicates the stimulation of erythropoiesis in these animals [5].…”
Section: Resultssupporting
confidence: 92%
“…It was found that the immunopathological process caused by the transfer of lymphocytes from one of the parental lines to hybrid mice can proceed both according to the Th2dependent developmental variant with the formation of lupus-like immunocomplex glomerulonephritis, and according to the Th1-dependent developmental variant -without nephritis, but with manifestations of severe immunodeficiency. As we have described earlier [5,11], an essential pathological component of cGVHD in this system is the presence of autoimmune hemolytic anemia caused by the production of large amounts of autoantibodies to own erythrocytes by activated B cells. However, the participation of platelets in this immunopathological process has not been studied, and there are no literature data on the behavior of platelets in cGVHD or on their relationship with the state of Th1/Th2 balance.…”
Section: т 25 №mentioning
confidence: 73%